Study guides

☆☆

Q: What is the answer to positive 6 subtract positive 7?

Write your answer...

Submit

Still have questions?

Related questions

-3

6

-13

35/6

you subtract the numbers then he higher number to start out with is the awnser. example: negative 3 - positive 7= 3-7=4 the higher number is 7 so i is positive. the final answer is positive 4

No a positive plus a positive is not a negative its a positive. because um lets say 6+7 there is no negative number so its just like regular adding.

7 times 6 is 42. If you subtract two, you get 42-2= 40.

5 - (-2) ______ 7 In this problem, it equals a positive because you do keep (5), change (- to +) change (- to + again). Keep, change, change. 6 - (-7) _____ 13 Again, we do keep (6), change (- to +), change (- to + again) So, positive.

6 - -2 = 8

1. Subtract 25 2. Then subtract 6 3. Then subtract 12 4. Then subtract 2 5. Then subtract 10 6. Then subtract 15 7. Then subtract 7 8. Then add 3 X 1/2 9. Then add 8

2

+ 6 means positive 6. -6 means negative 6. -5- (-6) means start with -5 and subtract (-6) . You subtract a negative number like you pay off a debt, so -(-6) means +6.

-2

to subtract a positive integer :move LEFT. The answer will get smaller

7 - 6 = 1

5 x 6 x 7 = 210. 210 is the answer. proof 210 - 5 = 205/5 = 41 210 - 6 = 204/6 = 34 210 - 7 = 203/7 = 29

-1/2+7/10

24

well, if it is a negative plus a positive, it would be much like subtracting backwards, like this: -4+7=3 or -11+7=-4 also, if it is a positive plus a negative, you subtract 4+(-7)=-3 or 11+(-7)=4

6/7 - 2/7 = 4/7

6 and 1/2

By implication numbers in mathematics are positive unless stated otherwise. Where confusion may arise the positive or negative sign is shown for purposes of clarity. (+6) - (-7) = ? This would normally be written as 6 - (-7) = ? If the "7" were a positive number then the result would be :- 6 - (+7) = 6 - 7 = -1, but "7" is a negative number and subtracting a negative number is equivalent to adding a positive number. So, (+6) - (-7) = 6 + (+7) = 6 + 7 = 13

-6 + 7 = 1.

6 - 7 = -1

Subtracting a positive number from any other number results in a lower value. For example, subtract 5 from 7: 7 - 5 = 2 It is exactly the same if the positive number is subtracted from a negative number. Subtract 5 from -3 for example: -3 - 5 = -8 The value of the result is lower and the result will always be negative.